Employment officers’ assessments of employment prospects for persons with physical disability: Structural discrimination on the basis of gender and country of birth - Dag, Munir; Kullberg, Christian (Disability Studies Quarterly, 2016)
This article concerns employment officers' assessments of persons with physical disabilities. The aim was to investigate the assessments made by employment officers of the motivation and ability to obtain, keep, and successfully perform a job, when young women and men, of Swedish and foreign country of birth, seek employment. The study is qualitative and data were collected via interviews supported by the vignette method. The respondents were eight employment officers working in employment offices in a large and a medium-sized municipality in Sweden. The results show that the employment officers assess the job seekers born in a foreign country (Iran) as less motivated to find a job and less motivated to work compared to those born in Sweden. The results also show that the applicants born in a foreign country are recommended to seek less-qualified jobs, and that women born in Sweden are recommended for more professional assistance and support to further education than other applicants. The study reveals the existence of negative ethnic discrimination in employment officers' assessments of employment prospects for persons with physical disabilities and indicates that improvements may be needed in the officers' understanding of how unconscious stereotypical expectations concerning disabilities, gender and ethnicity can affect their assessments and decisions. It is suggested that careful consideration should be given to whether pedagogic models that have been used in other contexts, for instance education, could be used as a complement in the management of cases in order to detect biases in assessments.